Attaining the 2030 Sustainable Development Goal of Sustainable Cities and Communities - Birdthistle, Naomi; Hales, Rob (Family Businesses on a Mission, 2024)
The ebook edition of this title is Open Access and freely available to read online. Attaining the 2030 Sustainable Development Goal of Sustainable Cities and Communities focuses on Sustainable Development Goal number eleven (SDG#11): making human settlements inclusive, safe, resilient, and sustainable. Examining family businesses in the Republic of Ireland, Germany, the United States, the United Arab Emirates, and Australia, each case study presents a unique perspective from their respective country, analysing how SDG#11 translates into creating and maintaining liveable home environments for all. The case studies presented generate insights and key takeaways into the role of family businesses in developing and encouraging sustainable practices that have a positive effect on every member of their community. The United Nations (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 which would help engender an improved, fairer, and more sustainable world - one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editors Naomi Birdthistle and Rob Hales bring together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia - such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations, and philanthropic centres - this book series appeals equally to those with a general interest in entrepreneurship and business.